Recent Progress on Electroactive Polymers: Synthesis, Properties and Applications - Md Hafizur Rahman; Harmony Werth; Alexander Goldman; Yuki Hida; Court Diesner; Logan Lane; Pradeep L. Menezes (Ceramics, 2021)
Electroactive polymers (EAPs) are an advanced family of polymers that change their shape through electric stimulation and have been a point of interest since their inception. This unique functionality has helped EAPs to contribute to versatile fields, such as electrical, biomedical, and robotics, to name a few. Ionic EAPs have a significant advantage over electronic EAPs. For example, Ionic EAPs require a lower voltage to activate than electronic EAPs. On the other hand, electronic EAPs could generate a relatively larger actuation force. Therefore, efforts have been focused on improving both kinds to achieve superior properties. In this review, the synthesis routes of different EAP-based actuators and their properties are discussed. Moreover, their mechanical interactions have been investigated from a tribological perspective as all these EAPs undergo surface interactions. Such interactions could reduce their useful life and need significant research attention for enhancing their life. Recent advancements and numerous applications of EAPs in various sectors are also discussed in this review.